PERAN STRATEGIS LEMBAGA KEUANGAN SYARIAH DALAM MENINGKATKAN KAPABILITAS EKONOMI PEREMPUAN RENTAN - Chelsy Namora Ahmad (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to analyze the strategic role of Islamic financial institutions (IFIs) in improving the economic capabilities of vulnerable women, particularly those in limited socioeconomic conditions. Using a qualitative-descriptive approach based on field studies, this research was conducted on several Islamic microfinance institutions such as Baitul Maal wat Tamwil (BMT) and Islamic cooperatives that actively channel financing to women microentrepreneurs. Data collection techniques included in-depth interviews, participatory observation, and documentation of the empowerment activities carried out by these institutions. The results show that LKS have a significant contribution in opening access to business capital, building women's confidence, and expanding family economic participation. Financing schemes based on the values of fairness, empathy, and transparency are the main strengths in building relationships that are not only transactional but also transformational. However, challenges remain in the form of limited sustainable assistance, lack of integration with other social programs, and the lack of outcome-based evaluation instruments. This study confirms that LKS not only function as fund providers but also as agents of social change that can strengthen the economic position of vulnerable women in a sustainable manner within the framework of maqāṣid al-sharī‘ah.